Impact of Symptomatic COVID-19 on the Oral Health of Pediatric Patients in Tbilisi City - Lia Mania; Ketevan Nanobashvili; Tinatin Manjavidze; Mamuka Benashvili; Nino Bzishvili; Ia Astamadze (Children)
Background/Purpose: Coronavirus disease 2019 (COVID-19) has become the cause of a global health crisis during the pandemic. This research aimed to study the impact of symptomatic COVID-19 on children’s oral health indices and salivary microbiome composition during the post-COVID-19 period. Methods: An observational, cross-sectional study was conducted in Tbilisi (Georgia) among children aged 7–12 years. A total of 421 children included in the study had a history of laboratory-confirmed COVID-19 within one year of exposure. No participants met the criteria for comorbid conditions or for PCC. A stratified simple random selection of schools and among selected clusters was used. The selected children were divided into two groups: the exposed group, who were patients with a history of symptomatic COVID-19, and the control group, who were patients with a history of asymptomatic COVID-19. The data were collected from August 2022 to December 2023. Oral screening, microbiological examination of saliva, and administration of questionnaires were also performed. Logistic regression was used to calculate ORs with 95% confidence intervals. The statistical processing of the data was performed with SPSS 23.0. This study was approved by the Biomedical Research Ethical Council of the University of Georgia (UGREC–04–22/9 March 2022). Results: Statistically significant differences in the means of the oral health indicators between the studied groups were detected (exposed: DMFT + deft = 5.9; MGI = 0.92; S-OHI = 1.9; control: DMFT + deft = 3.8; MGI = 0.56; S-OHI = 1.4). According to the logistic regression, symptomatic COVID-19 had a significant effect on the following oral health indicators: DMFT + deft (OR = 1.26; 95% CI = 1.14–1.39), MGI (OR = 2.31; 95% CI = 1.50–3.55), and S-OHI (OR = 3.43; 95% CI = 2.03–5.76). The effect of symptomatic COVID-19 on the frequency of eradication of the studied microbiome was also significant (OR = 2.12; 95% CI = 1.23–3.63). Conclusions: A close association was established between symptomatic COVID-19 and microbiome changes in the oral saliva of children, as well as between oral health indicators and symptomatic COVID-19. Considering the research results, it is assumed that a symptomatic course of COVID-19 may be an additional risk factor associated with poor oral health in the pediatric population in the post-COVID-19 period.